Comparison of Body Mass Index and Behavior of CERDIK of Individuals as Risk Factors of Suffering from Non-Communicable Diseases - Mugianti, Sri; Riyadi, Bastianus Doddy; Suyitno, Juin Hadi; Suprajitno, Suprajitno (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
Non-communicable diseases (NCDs) occur in individuals of the productive age and its risk can be diminished if such individuals possess healthy behaviors. BMI is a calculation which is frequently administered to express individuals at risk of suffering from NCDs. Predicting the risk of an individual from suffering from non-communicable diseases is possible by employing CERDIK behavioral (knowledge, attitude, and actions) questionnaires, but it does not yet elaborate the role of body mass index (BMI). The objective of this study is to compare the body mass index and behavior with individuals’ risk factors suffering from non-communicable diseases. The study administered a cross-sectional design. The sample amounted to 200 individuals in the productive age who generally fast-food establishments in Blitar from April to June of 2022. Sample was selected by administering the simple random sampling method. The results demonstrated that merely few individuals experienced a high risk of contracting non-communicable diseases. Behavioral factors are no longer used to determine an individual's risk of developing non-communicable diseases when body mass index is taken into account as a contributing factor. Therefore, body mass index is not a risk factor. According to research, adopting healthy lifestyle habits can lower the risk of developing non-communicable diseases.